Examining Pre-service Teacher Belief in Technological for Teaching Mathematics - Fitriani, Andhin Dyas; Darhim, Darhim; Juandi, Dadang (Mimbar Sekolah Dasar, 2024)
Technology is an effective learning tool. However, the existence of technology is an anxiety for teachers because it is difficult to follow. Therefore, this research intends to analyze teacher beliefs and teacher awareness of the role of technology, as well as the relationship between beliefs and teachers' pedagogical abilities regarding the use of technology in mathematics learning. This research was designed using a qualitative approach with a multiple case study design. Seven candidate elementary school teachers were involved in the research. Data collection was carried out through observation, interviews, and field notes. Data analysis was carried out using inductive and deductive analysis methods. The results of research studies showed that (1) teachers believe that technology can help maximum mathematics learning in the form of audio and visual words; (2) teachers realize that technology is an appropriate visualization tool in mathematics learning by adapting the form of visualization to be more detailed and appropriate to the child's character; (3) there is a relationship between teacher beliefs and candidate teachers' pedagogical abilities regarding the use of technology in mathematics learning. So, it can be concluded that teachers are confident and aware that technology has broad benefits in mathematics learning through its visualization form and there is a relationship between beliefs and teachers' pedagogical abilities in using technology.